MEPED as salvage therapy for relapsed/refractory Hodgkin’s lymphoma incorporating edited non-oncogene addiction: mTOR as a bottleneck - Harrer, Dennis Christoph; Lüke, Florian; Pukrop, Tobias; Ghibelli, Lina; Reichle, Albrecht; Heudobler, Daniel (Frontiers in Pharmacology, 2025)
Rescue therapies of relapsed/refractory (r/r) Hodgkin’s lymphoma (HL) in the third to sixth-line provide major, yet unresolved problems. The MEPED regimen includes nuclear receptor agonists such as pioglitazone and dexamethasone, which counterbalance HL homeostasis, HL stress response inhibitors, everolimus and COX-2 inhibitor, and a stress response inducer, low-dose metronomic treosulfan. CR (six of seven patients) and long-term cCR in patients receiving no consolidating allogeneic stem cell transplantation highlight MEPED as a potent salvage therapy in advanced refractory HL. MEPED edits everolimus activities in such a way that mTORC1 becomes a non-oncogene addiction bottleneck, hence determining long-term therapy outcome. The implications of the therapeutic paradigm shift toward editing of HL tissue, and particularly mTOR addiction, could prove to be profound for clinical practice, both in terms of outcome and treatment tolerability. The long-term results of MEPED treatment indicate the urgent evaluation of the schedule in a multicenter trial for r/r HL.